1995
DOI: 10.1007/bf00037118
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and cultivar identification of Jamaican yam germplasm by random amplified polymorphic DNA analysis

Abstract: We have used random amplified polymorphic DNA (RAPD) analysis to characterize eleven cultivars of the five economically most important yam species grown in Jamaica (Dioscorea alata, D . cayenensis, D . rotundata, D . trifida and D . esculenta) . Amplification of genomic DNA samples with nine different arbitrary 10mer primers revealed a total of 338 different band positions, ranging in size from 0 .3 to 2 .5 kb . RAPD patterns proved to be highly reproducible and somatically stable . While no variation was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 33 publications
(49 reference statements)
1
27
0
2
Order By: Relevance
“…rotundata was also studied using isozyme and morphological markers (Hamon and Toure, 1990;Zoundjihekpon et al, 1994;Dansi et al, 1999Dansi et al, , 2000aMignouna et al, 2002). Accessions of these species were also evaluated with random amplified polymorphic DNA, amplified fragment length polymorphism (Asemota et al, 1996;Dansi et al, 2000b;Mignouna et al, 2003), and simple sequence repeat markers (Scarcelli et al, 2005;Obidiegwu et al, 2009a). Mignouna et al (2005) concluded that cultivars that were classified as D. cayenensis should be considered as a taxon that was separate from D. rotundata.…”
Section: Introductionmentioning
confidence: 99%
“…rotundata was also studied using isozyme and morphological markers (Hamon and Toure, 1990;Zoundjihekpon et al, 1994;Dansi et al, 1999Dansi et al, , 2000aMignouna et al, 2002). Accessions of these species were also evaluated with random amplified polymorphic DNA, amplified fragment length polymorphism (Asemota et al, 1996;Dansi et al, 2000b;Mignouna et al, 2003), and simple sequence repeat markers (Scarcelli et al, 2005;Obidiegwu et al, 2009a). Mignouna et al (2005) concluded that cultivars that were classified as D. cayenensis should be considered as a taxon that was separate from D. rotundata.…”
Section: Introductionmentioning
confidence: 99%
“…The isozymatic genetic characterization in D. alata was performed by Lebot et al (1998) and Twyford (1990). This species was also studied with molecular markers such as RAPD, for the evaluation of resistance to anthracnose (Mignouna et al, 2002a) and genetic diversity studies (Asemota et al, 1996;Cheng and Liu, 1996;Zannou et al, 2009); AFLP, for the study of intraspecific genetic diversity (Egesi et al, 2006;Malapa et al, 2005) and development of a genetic map and analysis of QTL aimed at resistance to anthracnose (Mignouna et al, 2002b). Recently, Arnau et al (2009) used six microsatellite primers to study the segregation patterns from four different progenies of D. alata.…”
Section: Introductionmentioning
confidence: 99%
“…1). Other DNAbased molecular markers, such as simple sequence repeat (Muthamia et al, 2013 andNorman et al, 2012), random amplified polymorphic DNA, and amplified fragment length polymorphism (Asemota et al, 1996;Dansi et al, 2000;and Mignouna et al, 2003), were also used in the genetic diversity studies of yam.…”
Section: Discussionmentioning
confidence: 99%